Determination of three capsaicinoids in Capsicum annuum by pressurized liquid extraction combined with LC‐MS/MS. Issue 5 (4th February 2013) - Liu, Aili; Han, Chao; Zhou, Xiujin; Zhu, Zhenou; Huang, Fuzhen; Shen, Yan
<x xml:space="preserve">Abstract</x> A new method based on pressurized liquid extraction followed by LC‐MS/MS analysis has been developed for the identification and quantification of three capsaicinoids (capsaicin, dihydrocapsaicin, and nordihydrocapsaicin) in extracts of Capsicum annuum. For the recovery of three capsaicinoids, the efficiency levels of ultrasonic‐assisted extraction, microwave‐assisted extraction, Soxhlet extraction, and pressurized liquid extraction were compared under different conditions. Pressurized liquid extraction resulted in higher yields. Pressurized liquid extractions were performed using methanol; temperature was set at 100°C and pressure at 1500 psi. LC analysis was performed on a Waters XBridge™ C18 column (150 × 2.1 mm, id 3.5 μm) eluted by a mobile phase of 0.1% formic acid and ACN. Data acquisition was carried out in multiple reaction monitoring transitions mode, monitoring two‐reaction monitoring transitions to ensure an accurate identification of target compounds in the samples. The proposed method is rapid, simple, and could be utilized for the routine analysis of three capsaicinoids in C. annuum samples.